Age-restricted cervical screening: HPV testing at age 50 identifies a high risk group for cervical disease. Issue 6 (1st October 2002) - Cruickshank, M. E.; Chambers, G.; Murray, G.; Mckenzie, L.; Donaldson, C.; Andrew, J.; Campbell, M. K.; Kitchener, H. C.
Abstract : Changes to the present age policy of cervical screening are currently under consideration. We conducted a retrospective matched case-control study and cost analysis study to identify risk factors for the development of an abnormal smear after age 50 and to determine the impact of age-restricted cervical screening on the annual cost of the screening program. All women (229) from an 11-year birth cohort who developed an abnormal smear at age 50 or over were age-matched for two controls with negative smears. Routine screening smears taken between age 48 and 52 were tested for human papillomavirus (HPV) subtypes 16 and 18. Epidemiologic data were collected by postal questionnaire. Changes in costs under a policy of HPV testing and age-restricted screening were assessed. We found that HPV 16 status was the only independently significant risk factor for abnormal cytology after age 50 with an odds ratio of 10.26 (95% CI 1.25–84.11). A policy of early withdrawal from screening at age 50 on the basis of HPV testing would produce net cost savings. These findings suggest that HPV testing could be a valuable means of identifying the small proportion of women still at risk after 50, and of releasing health care resources.